Australia's Naval Modernization And Its Impact On Future Indo-Pacific Balance of Power - Ibrahim, Ahmad (Journal of Nautical Eye and Strategic Studies, 2024)
The research article examines the naval force modernization and strategic implications of Australia's rapidly expanding naval capabilities on Indo-Pacific power dynamics. Using theoretical lens of Balance of Power, article has evaluated how Canberra is expanding its power by enhancing military capabilities and by augmenting alliances with major powers. While Quad showcases multilateral co-operative arrangement between U.S., Australia, Japan, and India, it is AUKUS which is expected to impart major influence on future Indo-Pacific. With acquisition of nuclear attack submarines and development of advance naval combat capabilities, Canberra’s ability to project power across the Indo-Pacific is set to increase substantially. This modernization marks a shift from a predominantly defensive maritime posture toward a more assertive role. The article has provided overview of Australia’s current naval capabilities and has explored its naval modernization programs in all domain of naval warfare. It also analyses the broader geopolitical ramifications of Australia's growing naval strength, particularly in relation to AUKUS, within the Indo-Pacific region.